Male Sexual Abuse in Aydın - Pınarbaşılı, Raziye Didem Tuncer; Özkök, Mustafa Selim; Katkıcı, Ufuk; Erel, Özlem; Dirlik, Musa (The Bulletin of Legal Medicine, 2003)
To determine the properties of sexual abuse amony males in Aydm, 25 cases sent to Adnan Menderes University Department of Forensic Medicine, between 01.01.2003-31.12.2003 with claim of exposure to sexual abuse were evaluated with a questiannere were examined. The average age of victims was 16.1+7.7, the average age of first exposure to sexual abuse was 15.6+7.9 and it is harmonious with the age of male victims being assaulted. The age of being exposed to sexual abuse in male victims is simultaneous with psychosexual development period. The 48% of the victims expressed that their close friends or friends were exposed to sexual abuse too. In sexual abuse targeting males subjects the place of case is often open or deserted places, 88% of the victims knew who the suspect was. In 60% of the cases suspect and victim were hving in the same settlement. In most events in which victim is abused more than once, the suspect is the same person for each time. The reason of delayed complaints after a while is of his parents or relatives who notice the event in 76% of cases, Forensic Medicine Department is the first place of examination. Anal examination of 60% of the events, revealed no finding of.Key words: Sexual abuse, male, anal intercourse, victim, suspect, demographic changes
Keywords: sexual abuse; male; anal intercourse; victim; suspect; demographic changes